Phylogenomic characterization and pangenomic insights into the surfactin-producing bacteria Bacillus subtilis strain RI4914 - Ferreira, Julie Kennya de Lima; Varani, Alessandro de Mello [UNESP]; Totola, Marcos Rogerio; Almeida, Michelle Fernandes; Melo, Dirceu de Sousa; Batista, Cristina Ferreira Silva e; Chalfun-Junior, Antonio; Oliveira, Kellen Kauanne Pimenta de; Roesch, Luiz Fernando Wurdig; Pylro, Victor Satler (Springer, 2022)
Bacillus subtilis is a versatile bacterial species able to produce surfactin, a lipopeptide biosurfactant. We carried out the phylogenomic characterization and pangenomic analyses using available B. subtilis complete genomes. Also, we report the whole genome of the biosurfactant-producing B. subtilis strain RI4914 that was isolated from effluent water from an oil exploration field. We applied a hybrid sequencing approach using both long- and short-read sequencing technologies to generate a highly accurate, single-chromosome genome. The pangenomics analysis of 153 complete genomes classified as B. subtilis retrieved from the NCBI shows an open pangenome composed of 28,511 accessory genes, which agrees with the high genetic plasticity of the species. Also, this analysis suggests that surfactin production is a common trait shared by members of this species since the srfA operon is highly conserved among the B. subtilis strains found in most of the assemblies available. Finally, increased surfactin production corroborates the higher srfAA gene expression in B. subtilis strain RI4914.
Keywords: Biosurfactant; Nanopore sequencing; PGM IonTorrent; Whole genome sequencing; Hybrid assembly; GridIon